Sosialisasi Aplikasi Pengelolaan dan Penerimaan Bantuan Sosial Program Keluarga Harapan (PKH) di Kecamatan Sungai Keruh dengan Menggunakan Metode Simple Additive Weighting: Penelitian - Nur Jumriatunnisah; Indri Ariyanti; Dewi Irmawati; Aurantia Marina; M Zulkarnain; Tona Lestari; Firmansyah; Masayu Sarah Amelia (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
The goal of this community service is to realize the research activities conducted, which include socialization activities for the application of managing data on recipients of social assistance under the Family Hope Program (PKH) in the Sungai Keruh sub-district, so that this program runs effectively in terms of recording, monitoring, and evaluating PKH social assistance recipients. The data management application for Family Hope Program social assistance recipients uses the Simple Additive Weighting (SAW) Method, which is one of the decision-making methods widely used in decision support systems due to its ability to perform objective assessment calculations based on predetermined criteria. This approach process includes a recipient selection process that can be conducted transparently and measurably, taking into account various relevant assessment variables. Thus, data management becomes more accurate, systematic, and supports distribution.